The Effect of Using the Canva Application on Learning Outcomes Art Culture Class Student VII Junior High School 2 Pancarijang - Renaldi; Nurmayanti; Usman M; Hermansyah, Sam; Syamsunir (MultiTech Publisher, 2023)
This study aims to determine the effect of application usage Canva to Results Study Art Culture Student Class VII.1 SMPN 2 PANCARIJANG. Research This use method study quantitative with a random sampling research design with a posttest- only control group design Which aim For test Influence Use Application Canva to Results Study Art Culture Student Class VII.1 SMPN 2 Pancarijang. The population of this study were the 77 students of class VII.1 SMPN 2 with samples taken as many as 26 students of class VII.1 SMPN 2 and using random sampling technique. There are 2 variables in this study namely application usage Canva (independent variable) and Student Arts and Culture learning outcomes Class VII (dependent variable). Study this is implemented in class VII.1 Junior High School 2.Data collection techniques using documentation and tests. Results data The tests that have been collected are then analyzed using the mean and t-test formulas . Based on results analysis data, so obtained mark average group experiment = 83,461 And mark group control = 65,384 And on the t-test get T count 6,963> from T table 5% (2,064) and 1% (2,797) with db 24. Based on the results of the study it can be concluded that the hypothesis (H 1 ) is states the Effect of Using the Canva Application on Art Learning Outcomes Culture Student Class VII.1 SMPN 2 PANCARIJANG